Specific ANAMMOX activity (SAA) in a sequencing batch reactor: optimization test with statistical comparison - Bae, Hyokwan; Paul, Tanusree; Kim, Daeik; Jung, Jin-Young (SPRINGER, 2016)
A sequencing batch reactor (SBR) is a suitable system for evaluating an anaerobic ammonium oxidation (ANAMMOX) process. Response surface analysis was employed to optimize the specific ANAMMOX activity (SAA) and evaluate its technical features in a SBR with a range of total nitrogen (TN) concentration as NH4+-N and NO2--N at 1: 1 ratio and an appropriate pH. A partial cubic model adequately fit the response surface with high statistical significance. SAA was optimized at 1.77 mg-N/mg-VSS day with 155.9 mg-N/L TN concentration and pH at 7.34. The inhibition factors of free ammonia, free nitrous acid (FNA), and nitrite gave specific rise to the SAA responses of over 1.4 mg-N/mg-VSS day in square-like boundaries. However, the toxic effect of 2.4 mg-N/L of FNA was identified to induce a drastic decrease at the lowest pH of 5.6. For the most optimized fed-batch mode for ANAMMOX-SBRs, this study found that TN was 100-200 mg/L and pH was 6.5-8, which can become controlling factors for physicochemical reactions at the time of substrate feeding and microbial reacting stages.
Keywords: ANAEROBIC AMMONIUM OXIDATION; AUTOTROPHIC NITROGEN REMOVAL; MICROBIAL COMMUNITY STRUCTURE; START-UP; OXIDIZING MICROORGANISMS; LOW-TEMPERATURE; WASTE-WATER; SBR; ENRICHMENT; PERFORMANCE